Baseline mean and heterogeneity of MR cartilage T2 are associated with morphologic degeneration of cartilage, meniscus, and bone marrow over 3 years – data from the Osteoarthritis Initiative - Joseph, G.B.; Baum, T.; Alizai, H.; Carballido-Gamio, J.; Nardo, L.; Virayavanich, W.; Lynch, J.A.; Nevitt, M.C.; McCulloch, C.E.; Majumdar, S.; Link, T.M. (Osteoarthritis and cartilage, 2012)
The purpose of this study is to determine whether the mean and heterogeneity of magnetic resonance (MR) knee cartilage T(2) relaxation time measurements at baseline are associated with morphologic degeneration of cartilage, meniscus, and bone marrow tissues over 3 years in subjects with risk factors for osteoarthritis (OA). Subjects with risk factors for OA (n=289) with an age range of 45-55 years were selected from the Osteoarthritis Initiative (OAI) database. 3.0 Tesla MR images were analyzed using morphological gradings of cartilage, bone marrow and menisci whole-organ magnetic resonance imaging scores (WORMS scoring). A T(2) mapping sequence was used to assess the mean and heterogeneity of cartilage T(2) (gray level co-occurrence matrix texture analysis). Regression models were used to assess the relationship between baseline T(2) parameters and changes in morphologic knee WORMS scores over 3 years. The prevalence of knee abnormalities in the cartilage (P<0.0005), meniscus (P<0.00001), and bone marrow significantly (P<0.00001) increased from baseline to 3 years in all compartments combined. The baseline mean and heterogeneity of cartilage T(2) were significantly (P<0.05) associated with morphologic joint degeneration in the cartilage, meniscus and bone marrow over 3 years. The prevalence of knee abnormalities significantly increased over 3 years; increased cartilage T(2) at baseline predicted longitudinal morphologic degeneration in the cartilage, meniscus, and bone marrow over 3 years in subjects with risk factors for OA.